Effect of carbonated aggregates on the mechanical properties and thermal conductivity of eco-concrete. (10th February 2019) - Rahmouni, Imen; Promis, Geoffrey; R'mili, Abdelhamid; Beji, Hassen; Limam, Oualid
Highlights: New ecological concretes made with carbonated aggregates. Measurement of mechanical and thermal properties of eco-concretes studied. Prediction and validation of thermal conductivity with HAC model. Abstract: This paper presents a study on the effect of carbonated-aggregates on mechanical properties and thermal conductivity of eco-concretes. These carbon negative eco-aggregates are produced by accelerated carbonation where industrial by-products or incinerators' waste are combined with carbon dioxide (CO2 ). These manufactured aggregates have particular characteristics giving them a certain interest in the field of civil engineering such as in replacement of natural aggregates in concrete. Morphological, physical, mechanical and thermal characterizations were performed on eco-aggregates in order to use them in the production of concrete. Then, concretes based on these carbonated-aggregates were formulated. In the experimental program, different mixtures were prepared by partially replacing natural aggregates by carbonated ones resulting in concretes with unit weights varying between 1750 and 2290 kg/m 3 . For all produced concrete mixes, the water to cement (w/c) ratio was kept constant. Compressive strength, modulus of elasticity, thermal conductivity, water absorption and sorptivity were measured. Results have been compared to control concrete mixes produced using ordinary aggregates and expanded clay. The results show that the tested eco-concretes have sufficient mechanical strength and interesting thermal conductivity. Therefore, they could be used for construction projects.